2019
DOI: 10.1101/2019.12.15.876771
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Central Role for Canonical PRC1 in Shaping the 3D Nuclear Landscape

Abstract: Highlights:1. Loss of RING1B substantially disrupts nuclear architecture.2. PRC1 mediated looping can occur at a Mb scale and is independent of CTCF.3. Polycomb mediated looping is driven by canonical PRC1 complexes.4. Multimeric PRC1-mediated interactions occur in vitro and in vivo. Disruption of PRC1-mediated looping is independent of gene activation. AbstractPolycomb group (PcG) proteins silence gene expression by chemically and physically modifying chromatin. A subset of PcG target loci are compacted and c… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
47
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(51 citation statements)
references
References 86 publications
(170 reference statements)
4
47
0
Order By: Relevance
“…Polycomb loops link H3K27me3-modified loci from the same chromatin compartment that are separated by tens to hundreds of megabases on the linear chromosome, and they appear orthogonal to the ~1Mb size TADs based on CTCF and cohesin, indicating an intermediary structure in the hierarchical organization of 3D genome folding. This finding is consistent with studies that conclude that PRC-1 associated interactions are independent of CTCF and TADs 9,41 . While changes in enzymatic activity of PRC1 do not impair these interactions, our study demonstrates loss of Polycomb-associted interation when disrupting PRC2 RNA binding domain, suggesting there may be distinct roles for PRC1 and PRC2 in regulation of genome architecture 41 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Polycomb loops link H3K27me3-modified loci from the same chromatin compartment that are separated by tens to hundreds of megabases on the linear chromosome, and they appear orthogonal to the ~1Mb size TADs based on CTCF and cohesin, indicating an intermediary structure in the hierarchical organization of 3D genome folding. This finding is consistent with studies that conclude that PRC-1 associated interactions are independent of CTCF and TADs 9,41 . While changes in enzymatic activity of PRC1 do not impair these interactions, our study demonstrates loss of Polycomb-associted interation when disrupting PRC2 RNA binding domain, suggesting there may be distinct roles for PRC1 and PRC2 in regulation of genome architecture 41 .…”
Section: Discussionsupporting
confidence: 92%
“…These results suggest that long-range H3K27me3 loops may be independent units of genome architecture and are consistent with the observation that three-dimensional PcG genome architecture domains behave differently than CTCF/cohesin mediated domains 39 . Zhang et al 40 and Boyle et al 41 recently identified Polycomb associated long-range DNA loops by overlapping ChIP-seq of PRC2 or PRC1 marks respectively with HiC data acquired separately, which likely represent related phenomena. The addition of H3K27me3 HiChIP data in this work demonstrates that (i) H3K27me3 and the chromosome loops are present on the same chromatin fiber; (ii) Polycomb loops can be efficiently detected at ~1/10 th the sequencing cost compared to HiC (Supplementary Figure 2).…”
Section: Resultsmentioning
confidence: 99%
“…5c). In pluripotent cells, these PE-gene interactions are mediated by PcG complexes recruited to both oCGIs and pCGIs 8,9,82,83 and are likely to be dependent on the polymerization and/or phase separation properties of PRC1 [60][61][62]84 .…”
Section: Discussionmentioning
confidence: 99%
“…The lack of PE-gene contacts in Sox1(+35)CGI ESC can be attributed to the weaker recruitment of PRC1 to the PE in these cells (Extended Data Fig. 8b), since long-range interactions between PcG-bound loci are considered to be mediated by PRC1 [60][61][62][63] . Furthermore, the strong interactions between the PE Sox1(+35)TFBS+CGI insert and the Gata6 promoter were also observed upon differentiation into AntNPC (Extended Data Fig.…”
Section: Ocgis Increase the Physical And Functional Communication Betmentioning
confidence: 99%
See 1 more Smart Citation